Você está na página 1de 15

10 2 10 9 /cm

e E g /2k b T

V (r) V (r) = V (R + r) R

2

2m 2 + V (r) Ψ = Ψ

N1

Ψ nk ( r + R) = e i .R .Ψ nk ( r)

V (x) = α

δ(x ja)

0

0 < x < a

2

2m

2

d

d

2

dx 2 Ψ = EΨ

dx 2 Ψ = k 2 Ψ

k = 2mE

Ψ(x) = A.sin(kx) + B.cos(kx)

0 < x < a

Ψ(x) x = 0

 B = e −iKa [A.sin(ka) + B.cos(ka)] δ kA − e −iKa k[A.cos(ka) − B.sen(ka)] = 2mα 2 B sin(ka) cos(Ka) = cos(ka) + mα 2 k sin(ka)

z = ka

f (z)

f (z) = cos(z) + β sin(z)

z

f (z) β = 10

[1, 1] k K

1

e (Eµ)/kT + 1

f(E, T) =

E

ν(E)dE E E + dE

ν(E)dE = f (E, T )D(E)dE

D(E) T = 0 E f

H 0 |n

H 0 |n = E n |n

ˆ

W (t) Ψ(t)

Ψ(t) = a n (t)|n e iE n t/

n

|n E n = ω n

i

∂t

n

ˆ

i t Ψ(t) = (H 0 + W (t))Ψ(t)

a n (t)|n e iω n t = (H 0 + W (t)) a n (t)|n e iω n t

ˆ

n

i a n (t) t |n e iω n t = a n (t)H 0 |n e iω n t

n

n

i

n

e n t

t a n (t) = a n (t) W(t)|n e iω n t

ˆ

n

m| m|n

ˆ

d

i dt a m (t) = a n (t)W mn e iω mn t

n

W mn = m| W (t)|n H 0

n m a m

ω mn = E m E n

a m a n (t = 0) = 1

a m (t) =

i

1

t =t

t =0

W mn e iω mn t dt

E m

P n (t) = |a m (t)| 2 =

2

1

t =t

t =0

W mn e mn t dt

2 = |W mn | 2 e iω mn t 1

2

ω

mn

2

P n (t) = 2πt |W mn | 2 δ(E m E n )

E E + dE

P n (t) = 2πt |W mn | 2 D(E)δ(E m E n )dE

P n (t)

dP n (t)

= 2π

dt

|W mn | 2 D(E)

1

τ n

= 2π

|W mn | 2 D(E)δ(E m E n )

τ n |n

D

opt

3

(k)dk = 2 × 4πk 2

dk

(2π) 3 =

2

k

π 2 dk

n r k = n r ω/c

D

opt

3

(ω)= ω 2 n

3

r

π

3 c 3

S =

E × H/2

1

| S| = 2 c 0 | E 0 | 2

U(ω) =

1

2

0 | E 0 | 2

U(ω) = D

opt

3

(ω)f BE (ω) ω

f(E) =

1 1

ω

e k b T

U(ω) = ω 3 n

π

2 c 3

3

r

1

ω

e k b T

1

k E 1 E 2 |1 |2 |2 |1

E 2 = E g + 2m 2 k 2

e

m

e

E 1 = 2m 2 k 2

h

m h h

ω = E 2 E 1 = E g + 2 k 2

2

1

m

1

h

e

m

+

m r

1

m r

=

1

m

e

+

1

m

h

ω = E g + 2m 2 k 2

r

k

= ( ω E g ) 1/2 2m r

1/2

dk =

1

2 ( ω E g ) 1/2 2m r

1/2

D(E) = D( ω) =

2π 2 2m r

1

2

1/2 ( ω E g ) 1/2

E = ω = ck opt dk = cn r dk o pt

D

opt

3

(E)

=

2

π 2 E 3 c 3

n r (ω) E = ck opt /n r

P(E) = D

opt

3

(E)f(E) =

E 2 n

3

r

1

π 2 3 c 3

E

e k b T

1

E 21 = E 2 E 1

B 12 = 2π

|W 12 | 2

R est = B 12 P(E 21 )f 1 (1 f 2 )

R

R

12

est

21

esp

21

= B 21 P(E 21 )f 2 (1 f 1 )

= A 21 f 2 (1 f 1 )

R

est

12

= R

esp

21

+ R

est

21

B 21 = B 12

µ f i E i f i (1 f j )

P(E 21 ) =

A

21

B 21

= D

opt

3

A 21

B 21 (e E k b 2 T 1 1)

(E 21 ) =

E

2

21 n r

3

π 2 3 c 3

α ω

α =

R

est

12

R

est

21

S/ ω

S = (c/n r )P(E 21 ) µ

α

= n r B 12 (f 1 f 2 )

c

α

α =

R

esp

12

B 12 (f 1 f 2 )

A 21 f 2 (1 f 1 )

=

π

2 c 2 2

E

2

2

21 n r

R

esp

12

(e (E 21 µ)/k b T 1)

g α α < 0 f 1 < f 2 µ > E 21 f 2 f 1

f h = 1 f 1 f e = f 2

g( ω) = α( ω) = 2πn r |W 21 | 2

c

2π 2 2m r

1

2

3/2 ( ω E g ) 1/2 (f e + f h 1)

|W 12 |

E opt =

E 0 .e i opt . ωt

Ψ Ψ = U ek (x)e i( . )

W he = Ψ h | W|Ψ h = e| E| U

ˆ

hk (x)U ek (x)xe i( opt ) dx

= opt opt = W

g opt = g 0 ( ω E g ) 1/2 (f e + f h 1)

g 0 300K E g = 1.4eV g 0 = 2.64 × 10 4 cm 1 eV 1/2

D( )(f e + f h 1) = ω E g 4 × 10 19 cm 3

D( )(f e + f h 1) = ω E g

µ

I